PENATAAN MINI MARKET BERDASARKAN PP NOMOR 5 TAHUN 2021 TENTANG PENYELENGGARAAN PERIZINAN BERUSAHA BERBASIS RESIKO DI KABUPATEN BANGLI - Ni Made Puspasutari Ujianti; A.A Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum, Universitas Warmadewa, 2025)
The changes of lifestyle and consumption patterns of urban society, which increasingly demand convenience and practicality, has led to the rapid growth of supermarkets in Bangli Regency. Bangli Regency is beginning to thrive, following the lead of other regencies and cities in Bali Province. The rise in domestic tourist visits to Bangli Regency, which still offers beautiful natural landscapes and promising tourist destinations, has fueled the development of supermarkets. According to Government Regulation No. 5 of 2021 concerning the Risk-Based Business Licensing System, supermarkets are considered low-risk businesses, so their licensing procedures are simpler compared to businesses with medium or high risk. However, this regulation conflicts with the Bangli Regency Regional Regulation No. 1 of 2016 regarding the Protection and Organization of Traditional Markets, Shopping Centers, and Modern Stores. If this issue left unaddressed, this could lead to an overconcentration of supermarkets in Bangli Regency, which may, in turn, affect the existence of traditional markets.